KAJIAN KESESUAIAN LAHAN UNTUK TANAMAN PANGAN di DESA NEKAN KECAMATAN ENTIKONG KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT - Tience Elizabet Pakpahan (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2020)
The study of land suitability for food crops in Nekan village, entikong sub-district, Sanggau district, West Kalimantan province aims to analyze land suitability and limiting factors as well as efforts made to improve land suitability classes. This research was conducted from May to October 2018 in Nekan village, Entikong sub-district, Sanggau district, West Kalimantan province using a land survey method. The results of the study stated that the land suitability class for maize plants was S3 wa, r, nr with rainfall limiting factors, phosphorus and potassium, for cassava plants were S3 na, eh with slope limiting factors and Potassium. For sweet potato plants is S3 wa, na with limiting factors of water availability and nutrients. For peanut plants, namely N wa with a rainfall limiting factor. Improvement efforts made for maize plants include making drainage, liming, fertilizing SP-36 and KCl. Plant cassava by making a terrace and planting according to the contour lines and fertilizing KCl. Sweet potato plants, make draenase and fertilize Potassium and peanut plants by making draenase and arranging planting time